MORPHOLOGICAL FEATURES OF REPARATIVE PROCESSES IN THE RABBIT CORNEA AT INJECTION OF CRYOPRESERVED NUCLEATED CELLS OF CORD BLOOD ON THE BACKGROUND OF EXPERIMENTAL LIMBAL DEFICIENCY - Svidko, K.M.; Demin, Yu.A. (World of Medicine and Biology, 2013)
The morphological substantiation of advisability for the use of cryopreserved nucleated cells of cord blood to compensate for the limbal deficiency is in article. The acceleration of the processes of reparative regeneration of the corneal epithelium and restoring of its structure due to the migration and differentiation of stem cells are proved.